A Study of Abrasion Identification for Coastal Areas at Sidangoli Gam Village - Sidiq Setiawan; Suyuti Suyuti; Zulkarnain K. Misbah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
An abrasion of the coastal areas has occurred at Sidangoli Gam Village, West Halmahera of North Maluku. The original condition was planted mangroves for coastal areas protection. However, it has recently been abraded due to big waves from the Pacific Ocean. Local people and the government constructed a conventional dike using coral stone and wooden piles. Nonetheless, this dike construction is designed without physical meaning. On the other hand, local people cannot be moved to another location because they have fishermen, and this place is very familiar to them. This research aimed to study the identification factor of coastal abrasion area in the field, such as observation in length, abrasion in width, the measured elevation of land, taken coordinates by using GPS (Global Positioning System) for two points and measuring the slope of the land, lithology of the soil layer, land use, and also enquire about how long people have lived in the nearby coastline area. Therefore, the index of susceptibility to abrasion, called IKP, will be presented. The index of susceptibility of abrasion (CVI) results are obtained at 48,99, a moderate vulnerability condition. This value is considered as shoreline change of 4.0, visually observed of 5.0, abrasion in the length of 1.0, abrasion in width of 4.0, green belt width of 4.0, soil lithology of 4.0, land use of 4.0 and slope on land of 5.0. These results may be conducted using coastal dikes to avoid big and high waves from the Pacific Ocean.